2012
DOI: 10.1371/journal.pone.0032254
|View full text |Cite
|
Sign up to set email alerts
|

Food Chain Transport of Nanoparticles Affects Behaviour and Fat Metabolism in Fish

Abstract: Nano-sized (10−9–10−7 m) particles offer many technical and biomedical advances over the bulk material. The use of nanoparticles in cosmetics, detergents, food and other commercial products is rapidly increasing despite little knowledge of their effect on organism metabolism. We show here that commercially manufactured polystyrene nanoparticles, transported through an aquatic food chain from algae, through zooplankton to fish, affect lipid metabolism and behaviour of the top consumer. At least three independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
244
1
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 466 publications
(256 citation statements)
references
References 32 publications
5
244
1
6
Order By: Relevance
“…Cedervall et al (2012) showed that 25 nm nanopolystyrene particles were transported through an aquatic food chain from green algae (Scenedesmus sp. ), through water fleas (Daphnia magna) to carp (Carassius carassius) and other fishes, and affected lipid metabolism and behaviour of the fish.…”
Section: Bioaccumulation and Effects Of Nanoplasticsmentioning
confidence: 99%
“…Cedervall et al (2012) showed that 25 nm nanopolystyrene particles were transported through an aquatic food chain from green algae (Scenedesmus sp. ), through water fleas (Daphnia magna) to carp (Carassius carassius) and other fishes, and affected lipid metabolism and behaviour of the fish.…”
Section: Bioaccumulation and Effects Of Nanoplasticsmentioning
confidence: 99%
“…Additionally, plastic particles can adsorb and transport persistent organic "pollutants" such as polychlorinated biphenyls (PCBs) and dichlorodiphenyldichloroethylene (DDE, Hirai et al 2011;Teuten et al 2009). The mere presence of toxic substances and persistent organic pollutants on microplastics enhances the risk of bioaccumulation since the particles could be incorporated by living organisms (Cedervall et al 2012;Andrady 2011;Gouin et al 2011). This is even more likely for microscopic plastic fragments (Graham and Thompson 2009;Browne et al 2008; Thompson et al 2004).…”
mentioning
confidence: 99%
“…However, it has also been observed that nanosized plastic particles are found in the circulatory systems and translocated to the fish liver (Avio et al, 2015b). In addition, it has been found that such exposure to nanoparticles can change fish metabolism (Cedervall et al, 2012). Plastic exposure has also been found to change gene expression for example up-regulation of fatty acids and down regulation of amino acids (Lu et al, 2016) while also other impacts following microplastic exposure have been found, such as hepatic stress .…”
Section: Effects Of Ingestion On Fish and Invertebrates From Laboratomentioning
confidence: 99%